Development and Transfer of Microbial Agrobiotechnologies in Contrasting Agrosystems: Experience of Kazakhstan and China - Aimeken M. Nygymetova; Assemgul K. Sadvakasova; Dilnaz E. Zaletova; Bekzhan D. Kossalbayev; Meruyert O. Bauenova; Jingjing Wang; Zhiyong Huang; Fariza K. Sarsekeyeva; Dariga K. Kirbayeva; Suleyman I. Allakhverdiev (Plants, 2025)
The development and implementation of microbial consortium-based biofertilizers represent a promising direction in sustainable agriculture, particularly in the context of the ongoing global ecological and agricultural crisis. This article examines the agroecological and economic impacts of applying microbial consortiums and explores the mechanisms of technology transfer using the example of two countries with differing levels of scientific and technological advancement–China and Kazakhstan. The analysis of the Chinese experience reveals that the successful integration of microbial biofertilizers into agricultural practice is made possible by a well-established institutional framework that includes strong governmental support for R&D, a robust scientific infrastructure, and effective coordination with the private sector. In contrast, Kazakhstan, despite its favorable agroecological conditions and growing interest among farmers in environmentally friendly technologies, faces several challenges from limited funding to a fragmented technology transfer system. The comparative study demonstrates that adapting Chinese models requires consideration of local specificities and the strengthening of intergovernmental cooperation. The article concludes by emphasizing the need to establish a multi-level innovation ecosystem encompassing the entire cycle of development and deployment of microbial biofertilizers, as a prerequisite for improving agricultural productivity and ensuring food security in countries at different stages of economic development.